2011
DOI: 10.1186/1479-0556-9-2
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus genotype 3a with phylogenetically distinct origin is circulating in Pakistan

Abstract: BackgroundHepatitis C virus (HCV) is one of the leading causes of viral hepatitis worldwide and its genotype 3a is predominant in vast areas of Pakistan.FindingsThe present study reports the first full sequence of HCV 3a isolate PK-1 from Pakistan. This nucleotide sequence was compared with six other HCV genotype 3a full length sequences from different regions of the world by using statistical methods of phylogenetic analysis.ConclusionThe nucleotide difference of these seven sequences shows that HCV genotype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 14 publications
(17 reference statements)
4
20
0
Order By: Relevance
“…There was a wide range of ages for the commencement of IDU (14 to 39 years of age), although the mean, median, and mode (21,19, and 19 years, respectively) ages of these individuals confirmed that older age groups were unusual. This was applied to all other samples in the Scottish data set to give the estimated year of infection (EYI) for these individuals and used in the phylogeographical analysis within Scotland.…”
Section: Methodsmentioning
confidence: 97%
“…There was a wide range of ages for the commencement of IDU (14 to 39 years of age), although the mean, median, and mode (21,19, and 19 years, respectively) ages of these individuals confirmed that older age groups were unusual. This was applied to all other samples in the Scottish data set to give the estimated year of infection (EYI) for these individuals and used in the phylogeographical analysis within Scotland.…”
Section: Methodsmentioning
confidence: 97%
“…The current standard is the INNO-LiPA, a line probe reverse hybridization assay that uses probes to the 5' untranslated region (UTR) and part of the core sequence to discern HCV type (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations have shown that HCV GT distribution varies worldwide (10,11), though less is known about HCV subtypes. HCV subtype sequences have been shown to cluster on phylogenetic trees based on region of origin (12)(13)(14). Potentially, the diversification of HCV in local epidemics could affect SVR rates if resistance associated substitutions (RASs) emerge.…”
Section: Introductionmentioning
confidence: 99%
“…In other subtypes, HCV-2a and 2b subtypes are mostly common in North America, Europe and Japan, and subtype 2c is found commonly in northern Italy [9]. HCV subtype 3a is the most common genotype circulating in India, Nepal and Pakistan [20]. In the other types of HCV, genotype 4 is common in the Middle East, and in Africa, HCV genotype 5 and HCV genotype 6 are establish only in South Africa and Hong Kong, respectively [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…While genotype 3a is very sensitive to interferon medication compared to the other genotypes, genotype 1b is more resistant to interferon in HCV genotypes [20,21]. In Europe and in North and South America, HCV subtypes 1a and 1b have been reported as the most prevalent genotype, likewise subtype 1b is responsible in most of HCV infection in Japan [9,13].…”
Section: Discussionmentioning
confidence: 99%